1999
DOI: 10.1677/erc.0.0060197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aromatase inhibitors on the pathobiology of the human breast, endometrial and ovarian carcinoma.

Abstract: It is very important to examine the influence of inhibition of in situ estrogen production on the pathobiology of human sex steroid-dependent tumors in order to understand the clinical effects of aromatase inhibitors. We have examined the biological changes before and after aromatase inhibitor treatment in vitro (endometrial and ovarian cancer) and in vivo (breast cancer). First, we analyzed these changes using histoculture of 15 human endometrial cancers and 9 ovarian cancers. Five of the fifteen endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…We previously examined the biological changes in endometrial carcinoma tissues before and after aromatase inhibitor treatment. Five of 15 human endometrial carcinoma demonstrated decreased [ 3 H] thymidine uptake or Ki-67 labeling following aromatase inhibitor treatment [22]. Berstein et al reported similar results [63].…”
Section: ) Aromatase Inhibitormentioning
confidence: 84%
See 2 more Smart Citations
“…We previously examined the biological changes in endometrial carcinoma tissues before and after aromatase inhibitor treatment. Five of 15 human endometrial carcinoma demonstrated decreased [ 3 H] thymidine uptake or Ki-67 labeling following aromatase inhibitor treatment [22]. Berstein et al reported similar results [63].…”
Section: ) Aromatase Inhibitormentioning
confidence: 84%
“…This positive linkage indicates that local aromatase expression plays a role in tumor progression through the formation of in situ estrogens. In addition, we previously reported that an aromatase inhibitor suppressed the proliferation of endometrial carcinoma cells, which exhibited aromatase activities in vitro [22]. Aromatase is considered a key enzyme in the synthesis of estrogen in endometrial carcinoma as well as breast carcinoma.…”
Section: ) Aromatasementioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with anastrozole caused a marked decrement in proliferation as demonstrated by decreased Ki-67 expression. Sasano previously reported similar results using [ 3 H] thymidine uptake or Ki-67 labeling (Sasano et al 1999). Therefore, it is important to clarify the roles, including the possibility of application and indication, of aromatase-inhibitory drugs in hormone-receptor positive or hormone-sensitive endometrial carcinoma in postmenopausal patients.…”
Section: Androgen Action From the Viewpoint Of Therapeutic Targetmentioning
confidence: 72%
“…Aromatase inhibitors are now widely used in treatment of estrogen-dependent breast cancer. 14,23,24 Aromatase inhibitors reduce estrogen levels by inhibiting estrogen synthesis in both tumor tissues and peripheral sites, and as a consequence they inhibit the proliferation of the tumor. Aromatase inhibitors may also influence apoptosis.…”
Section: Discussionmentioning
confidence: 99%